Integracja kulturalna Euroregionu "Nysa" (pogranicze polsko-czesko-niemieckie) na przełomie XX i XXI wieku na przykładzie "Nowin Jeleniogórskich" i innych źródeł = The cultural integration of the Nysa Euroregion (Polish-Czech-German borderland) at the turn of the 20th and 21st centuries on the example of "Nowiny Jeleniogorskie" - Skotnicka, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The Euroregion "Nysa" came into existence on December 21st, 1991 in Zittau and comprises border areas of three states: Poland, the Czech Republic and Germany. The cultural integration within the Euroregion "Nysa" includes numerous activities initiated by two or three states in many domains, for example: art, music, theatre, photography. The activities play a particularly significant role in learning more about one another, allow for the cooperation between schools, local government authorities and better integration of the local population.
Keywords: integracja kulturalna; Euroregion "Nysa"; pogranicze polsko-czesko-niemieckie